NI956/QGC006, a Potent Orally Active, Brain-Penetrating Aminopeptidase A Inhibitor for Treating Hypertension. Issue 6 (June 2019) - Keck, Mathilde; De Almeida, Hugo; Compère, Delphine; Inguimbert, Nicolas; Flahault, Adrien; Balavoine, Fabrice; Roques, Bernard; Llorens-Cortes, Catherine
Abstract : Brain renin-angiotensin system hyperactivity has been implicated in the development and maintenance of hypertension. We have shown that aminopeptidase A is involved in the formation of brain angiotensin III, which exerts tonic stimulatory control over blood pressure in hypertensive deoxycorticosterone acetate-salt rats and spontaneously hypertensive rats. We have also shown that injection of the specific and selective aminopeptidase A inhibitor, (3S)-3-amino-4-sulfanyl-butane-1-sulfonic acid (EC33), by central route or its prodrug, RB150/firibastat, by oral route inhibited brain aminopeptidase A activity and blocked the formation of brain angiotensin III, normalizing blood pressure in hypertensive rats. These findings identified brain aminopeptidase A as a potential new therapeutic target for hypertension. We report here the development of a new aminopeptidase A inhibitor prodrug, NI956/QGC006, obtained by the disulfide bridge-mediated dimerization of NI929. NI929 is 10× more efficient than EC33 at inhibiting recombinant mouse aminopeptidase A activity in vitro. After oral administration at a dose of 4 mg/kg in conscious deoxycorticosterone acetate-salt rats, NI956/QGC006 normalized brain aminopeptidase A activity and induced a marked decrease in blood pressure of −44±13 mm Hg 4 hours after treatment ( P< 0.001), sustained over 10 hours (−21±12 mm Hg; P< 0.05). Moreover, NI956/QGC006 decreased plasma arginine-vasopressin levels, and increased diuresis and natriuresis, that may participate to the blood pressure decrease. Finally, NI956/QGC006 did not affect plasma sodium and potassium concentrations. This study shows that NI956/QGC006 is a best-in-class central-acting aminopeptidase A inhibitor prodrug. Our results support the development of hypertension treatments targeting brain aminopeptidase A. Abstract : Supplemental Digital Content is available in the text.